Aurora kinase inhibitor restrains STAT5‐activated leukemic cell proliferation by inducing mitochondrial impairment. Issue 11 (2nd April 2020) - Wang, Jin‐Xing; Zhang, Ling; Huang, Ze‐Wei; Zhang, Xue‐Ning; Jiang, Yan‐Yan; Liu, Fang‐Jie; Long, Liang; Xue, Man‐Jie; Lu, Gui; Liu, Quentin; Long, Zi‐Jie
Abstract: Current chemotherapy regimens on acute myeloid leukemia (AML) still have some drawbacks, such as intolerance and drug resistance, which calls need for the development of targeted therapy. Signal transducer and activator of transcription 5 (STAT5) is often overexpressed or abnormally activated in leukemia and involved in cell self‐renewal, proliferation, and stress adaptation. Overexpressed Aurora A (AURKA) is associated with poor prognosis in tumors, and inhibitors against AURKA are already in clinical trials. However, it has rarely been reported whether AURKA inhibitors restrain STAT5‐activated leukemia cells. In this study, we constructed STAT5 constitutively activated (cS5) cells and found that STAT5 promoted cell proliferation and colony formation. Moreover, cS5 cells showed elevated reactive oxygen species (ROS) and adenosine triphosphate (ATP) levels, which indicated higher mitochondrial metabolism in cS5 cells. A novel AURKA inhibitor AKI604 was synthesized and showed significant inhibitory effects to the proliferation and colony formation in both STAT5 constitutively activated and nonactivated AML cells. AKI604 induced mitochondrial impairment, leading to the disruption of mitochondrial membrane potential and the elevation of ROS as well as cellular calcium (Ca 2+ ) levels. AKI604 could also decline basal oxygen consumption rate and ATP biosynthesis, indicating the damage of oxidative phosphorylation. Furthermore, AKI604 exhibited significant antitumor effect in the HL‐60 cS5 xenograft model of the BALB/c nude mice without an obvious influence on mice body weight and other healthy indicators. This study suggested that AKI604 was a potential strategy to overcome STAT5‐induced leukemic proliferation in AML treatment by inducing mitochondrial impairment. Abstract : AKI604 exhibited significant antitumor effect both in vitro and in vivo by inducing mitochondrial impairment.